Flavonols from the Ripe Fruits of Opuntia ficus‐indica Var. saboten Protect Neuronal PC‐12 Cells against Oxidative Stress. Issue 5 (19th September 2014) - Son, Jung‐Eun; Lee, Bong Han; Nam, Tae Gyu; Im, Sungbin; Chung, Dae Kyun; Lee, Jung Min; Chun, Ock K.; Kim, Dae‐Ok
Abstract Fruits of prickly pear cactus Opuntia ficus‐indica have been traditionally used as a folk medicine with various pharmacological activities, partly due to their antioxidative flavonoids. The ripe fruits of O. ficus‐indica var. saboten were extracted with 70% v/v aqueous ethanol to obtain phenolic extracts, which were separated into five fractions of n‐hexane, chloroform, ethyl acetate, n‐butanol and water. The ethyl acetate fraction showed the highest levels of total phenolics, total flavonoids and antioxidant capacity among the fractions tested. A reversed‐phase high‐performance liquid chromatography and quadrupole time‐of‐flight liquid chromatography‐mass spectrometry analysis of the ethyl acetate fraction revealed seven major flavonols: isorhamnetin‐3‐O‐glucoside, isorhamnetin‐3‐O‐rutinoside, kaempferol, kaempferol‐3‐O‐glucoside, kaempferol‐7‐O‐neohesperidoside, quercetin and quercetin‐3‐methylether. The ethyl acetate fraction increased the in vitro viability of neuron‐like PC‐12 cells against intracellular oxidative stress in a dose‐dependent manner. These results suggest that the ethyl acetate fraction rich in flavonols protecting neuronal cells from oxidative stress may be utilized as a functional food ingredient for nutraceuticals. Practical Applications Fruits of Opuntia ficus‐indica var. saboten are edible berries with a thick skin and many seeds, and have long been used as an oriental folk medicine with various health‐promoting effects, in part due to antioxidative phenolics. Antioxidative flavonols such as isorhamnetin, kaempferol and quercetin in the O. ficus‐indica var. saboten ripe fruit were identified and quantified as major phenolics, indicating that its extract can be standardized to use as an antioxidant source for product development in food manufacture. The O. ficus‐indica var. saboten ripe fruit phenolics attenuated intracellular oxidative stress and reduced the release of intracellular lactate dehydrogenase in the cytosol of neuron‐like PC‐12 cells. Therefore, the ethyl acetate fraction rich in flavonols might be utilized as a food ingredient for nutraceuticals.